Diet and Alzheimer's disease. - Luchsinger, José A; Noble, James M; Scarmeas, Nikolaos (Curr Neurol Neurosci Rep, 2007)
Alzheimer's disease (AD) is increasing in prevalence. There are no known preventive or curative measures. There is evidence that oxidative stress, homo-cysteine-related vitamins, fats, and alcohol have a role in the pathogenesis of AD. Some epidemiologic studies suggest that higher dietary intake of antioxidants, vitamins B(6), B(12), and folate, unsaturated fatty acids, and fish are related to a lower risk of AD, but reports are inconsistent. Modest to moderate alcohol intake, particularly wine, may be related to a lower risk of AD. The Mediterranean diet may also be related to lower AD risk. However, randomized clinical trials of supplements of vitamins E, B(12), B(6), and folate have shown no cognitive benefit, and randomized trials for other nutrients or diets in AD are not available. The existing evidence does not support the recommendation of specific supplements, foods, or diets for the prevention of AD.
Keywords: Alzheimer Disease; Antioxidants; Brain; Caloric Restriction; Diet Therapy; Dietary Fats; Food, Formulated; Homocysteine; Humans; Oxidative Stress; Randomized Controlled Trials as Topic; Vitamins